Behavior of the anti-apoptotic BCL-2 protein in non-small-cell lung cancer cell models in response to treatments with ALK inhibitors and its potential dual BCL2ALK inhibition - Zapata, Richard (2024)
Objective: To describe the behavior of the BCL-2 protein in non-small-cell lung cancer cell models in response to treatment with ALK (anaplastic lymphoma kinase) protein tyrosine kinase inhibitors (crizotinib and alectinib) and their potential dual BCL-2-ALK inhibition. Materials and methods: Three non-small-cell-lung cancer cell models were used: Ba/f3 EML4-ALKWT, Ba/f3 EML4-ALKL1196M and Ba/f3 EML4-ALKG1202R, generated by site-directed mutagenesis. These were treated with crizotinib and alectinib in a dose-responsive manner, and an apoptosis assay was also conducted to confirm pharmacological susceptibility. Subsequently, BCL-2 protein expression was measured under three treatment conditions (no treatment, 100 nM crizotinib and 50 nM alectinib). Finally, a search for BCL-2 and ALK ligands was performed for molecular docking simulation and interaction energy calculation, measured in kcal/mol in the YASARA™ program. Results: The WT model evidenced sensitivity to crizotinib and alectinib, with apoptosis percentages of 23 % and 74 %, respectively; G1202R showed resistance to both drugs (apoptosis: 5 %), and L1196M resistance to crizotinib (apoptosis: 12 %) and sensitivity to alectinib (apoptosis: 25 %). BCL-2 expression revealed overexpression in the WT and G1202R models, while L1196M showed expression close to baseline. Finally, bioinformatics findings identified ABT-199 (which is part of small molecule libraries) as the best candidate to inhibit BCL-2, while its interaction with ALKL1196M revealed interaction energies higher than those obtained in the interaction with crizotinib and alectinib. Conclusions: The cell models exhibited the pharmacological susceptibility described in the literature, BCL-2 expression during treatments remained overexpressed in WT and G1202R, while L1196M showed no variation. Finally, bioinformatics f indings suggest ABT-199 as a potential dual action inhibitor due to its higher interaction energy with ALK.